2018
DOI: 10.1002/sia.6588
|View full text |Cite
|
Sign up to set email alerts
|

Tribological properties of Ti‐doped diamond‐like carbon coatings under dry friction and PAO oil lubrication

Abstract: Titanium‐doped diamond‐like carbon (Ti‐DLC) coatings with Ti concentration of 4 at.% (Ti4at.%‐DLC) and 27 at.% (Ti27at.%‐DLC) were prepared by a hybrid ion beam deposition system for comparison. The tribological behaviors of Ti‐DLC coatings under dry friction and boundary lubrication conditions were systematically investigated. Results showed that, under dry friction, the Ti4at.%‐DLC coating displayed lower friction coefficient (0.07) and wear rate due to the continuous transfer film formed in the sliding inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 35 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…We measured a hardness value of 22.5 GPa for ta-C:Ti coated tool, in agreement with the results found at lower critical load (10 mN) in the scientific literature. 23,45 According to this study, the ta-C:Cr coated tool exhibited a hardness value of 18.41 GPa. This figure surpasses the measurement reported by Fiaschi et al, which ranged from 2.5 to 3.5 GPa at a 100 mN load.…”
Section: Coating Characterizationmentioning
confidence: 72%
See 1 more Smart Citation
“…We measured a hardness value of 22.5 GPa for ta-C:Ti coated tool, in agreement with the results found at lower critical load (10 mN) in the scientific literature. 23,45 According to this study, the ta-C:Cr coated tool exhibited a hardness value of 18.41 GPa. This figure surpasses the measurement reported by Fiaschi et al, which ranged from 2.5 to 3.5 GPa at a 100 mN load.…”
Section: Coating Characterizationmentioning
confidence: 72%
“…Research on the effect of alloying ta-C with transition metals like Ti 23,24 and Cr 20 was already been tried by researchers. Ta-C is a brittle ceramic, and alloying with stable carbide-forming metals causes the growth of nanoscale carbide inclusions, which make the material harder [22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Wu et al [17] reported that a modified graphene additive exhibited great lubrication performance under RSM, attributing it to the sliding-induced formation of nanostructured tribo-film. Guo et al [18] found that under dry RSM, Ti 4at.% -DLC coating had better tribological characteristics, which were attributed to the transfer film and graphitized carbon layer, while the wear of Ti 27at.% -DLC was dominated by titanium hard phase compounds at the contact interface, resulting in serious abrasive wear. It is obvious that most of the research has only focused on the tribological performance of materials under a single RSM or USM.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Guo et al investigated Ti-DLC films prepared by a hybrid ion beam deposition system, which exhibited lower friction coefficient (0.07) and wear rate of 1.12 Â 10-16 m 3 N À1 m À1 . [28] Electrodeposition as a modern technology has attracted attention due to its simple experimental equipment, the possibility of depositing complex shapes, and unique economics. [29,30] Particularly, the liquid-phase electrodeposition technique makes the liquid phase remains in a nonequilibrium state at low temperatures, which is conducive to the formation of new metastable phases, greatly reducing residual stresses and improving the quality of the films.…”
Section: Introductionmentioning
confidence: 99%